Eliokarmos craibii (Asparagaceae, Scilloideae), a new species from Pella se Berge, Northern Cape Province, South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Pinter, Michael; Wetschnig, Wolfgang (Phytotaxa, 2015)
Within the framework of a taxonomic revision of the genus Eliokarmos we here describe a new species from Pella se Berge in South Africa. Eliokarmos craibii sp. nov. is at first sight related to E. decus-montium and E. pendens, but the former can be clearly differentiated by the 2(−3) succulent, appressed, proteranthous leaves with lateral portions bent upwards, giving the appearance of thickened raised margins; the dimorphic filaments; the yellow ovary which is slightly verrucose in the upper half and white below; and the pyriform, apiculate seeds with papillate testa. A complete description is presented for this species, and data on morphology, ecology, and distribution are reported. Affinities and divergences with E. decus-montium and E. pendens are also discussed.